Pemaknaan Teologis M. Fethullah GÃ¼len tentang Relasi Agama dan Sains - Billa, Mutamakkin (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2011)
The article discusses Gülen?s theological perspective on relation between science and Islam, which becomes the platform of his educational movement?while within Islamic knowledge tradition (theology) this matter is still debated?mainly in terms of the position and relation between reason and revelation (wahy). Gülen is interested in defending the position of Islamic theology towards science and knowledge, which has so far?as he concluded?played subordinate role. Religion and science, to Gülen, cannot be considered equal in Islam. Gülen asserts that Muslims have not so far developed yet the concept of knowledge in its true meaning; based on Islamic values and formulated mainly from the Qur?an and the Prophet Muhammad?s deeds. Moreover, Gülen emphasizes that the assumption of separation of revelation and reason, which has been understood so far, has been in fact a false supposition. The clash that should exist is, in fact, between secular view and religious one.